High performance concrete in aggressive environment for sustainable design [electronic resource] - Lo, Siew Chang, 1987- , author (2011)
Project Paper (Sarjana Muda Kejuruteraan (Awam - Struktur dan Bahan)) - Universiti Teknologi Malaysia, 2011